Konservatisme Akuntansi: Financial Distress dan Debt to Equity Ratio - Ardy Sulistyo Putra; Hendy Satria (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
This purpose of this study was to analyze the effect of Financial Distress and Debt To Equity Ratio on the principle of accounting conservatism in transportation sector companies listed on the Indonesia Stock Exchange. This research method uses quantitative methods with cross section and time series data, data obtained from the IDX for three years from 2018-2020. Data processing was tested statistically through classical assumptions, multiple regression analysis and hypothesis testing with t test, F test and determination test. The results of this study indicate that financial distress partially does not affect the principle of accounting conservatism. Meanwhile, the debt to equity ratio partially has a negative and significant effect on the principle of accounting conservatism. Simultaneously prove that financial distress and debt to equity ratio have an influence on the principle of accounting conservatism